Enhancing the Mechanical and Thermal Properties of PEEK/PEI Composites: The Role of Talc and Titanium Dioxide Fillers in a Melt Mixing-Based Method - Arican, Selin; Salt, Inci (WILEY, 2025)
High-performance polymers such as polyether ether ketone (PEEK) and polyetherimide (PEI) are extensively employed in a wide range of applications requiring high temperature resistance and mechanical strength. Although high-performance polymers have superior properties, their mechanical and thermal properties can be further improved by using various fillers. The presence of these components within the polymer matrix has a significant impact on the properties of composite materials. In the present study, the effects of the PEEK/PEI ratio (80/20, 50/50 and 20/80 wt%) in the polymer blend, and the talc (T) and TiO2 (TD) fillers on the physical, mechanical, and thermal properties of the mineral-filled PEEK/PEI composites produced using a co-rotating twin-screw extruder were investigated. The developed high-performance polymer composites were characterized by means of melt flow index (MFI), mechanical strength tests, DSC, TGA, DMA, and SEM. The MFI decreased with higher PEI content; however, the incorporation of mineral fillers did not negatively affect the fluidity. Increased PEI content improved tensile strength, while inorganic fillers enhanced the tensile modulus compared to neat PEEK. TGA and DSC analyses revealed that mineral-filled composites maintain thermal stability at elevated temperatures. SEM analysis confirmed a single polymer phase and uniform filler distribution, with no agglomeration observed.
Keywords: melt mixing; polyether ether ketone; polyether imide; polymer composites; talc; TiO2; POLY(ETHER ETHER KETONE); CRYSTALLIZATION BEHAVIOR; TRIBOLOGICAL BEHAVIOR; MISCIBLE BLENDS; MISCIBILITY; SEMICRYSTALLINE; NANOCOMPOSITES; IMIDE); Engineering; Polymer Science